INDIAN SEED SECTOR - CHALLENGES AND OPPORTUNITIES - T. PRADEEP, M.V. NAGESH KUMAR, Y. BHARATHI AND (The Journal of Research, PJTSAU, 2019)
Seed is a bridge of hope between present and future and is inevitable for life’s continuity. India has a vibrant seed market. Over the years, the seed industry has evolved side by side with Indian agriculture. From the practice of saving seeds from the previous crop, Indian farmers have come a long way. Today, the Indian seed industry is the fifth largest seed market in the world, accounting for 4.4% of global seed market. In terms of global trade, India is almost self-sufficient in flower, fruits and vegetables and field crops seeds. Overall, paddy, maize and vegetables are expected to drive the growth of Indian hybrid seed industry in the next five years. The government’s policy support has also gone a long way in supporting the seed industry’s evolution and development. From the Seed’s Act of 1966 to the Seed’s Bill 2004, India’s seed policy has been suggestive of India’s evolving needs and market dynamics. Conducive policy reforms and government support has spurred the transformation of this industry in recent times. Private seed sector has played a major role in changing Indian seed sector. Investment and technical expertise garnered from different parts of the world has made this fete possible. This review emphasizes on evolving of Indian seed sector, its growth, future challenges and expansion to export market.